Income polarization and economic growth - Michal Brzezinski (Luxembourg Income Study (LIS), 2013)
This study examines empirically the impact of income polarization on economic growth in an unbalanced panel of more than 70 countries during the 1960-2005 period. We calculate various polarization indices using existing micro-level datasets, as well as datasets reconstructed from grouped data on income distribution taken from the World Income Inequality Database. The results garnered for our preferred sample of countries suggest that income polarization has a negative impact on growth in the short term, while the impact of income inequality on growth is statistically insignificant. Our results are fairly robust to various model specifications and estimation techniques.
Keywords: O11; O15; O4; D31; 330; economic growth; polarization; inequality; income distribution; Einkommensverteilung; Index; Berechnung; Wirtschaftswachstum; Welt